2010
DOI: 10.1007/s10900-010-9296-8
|View full text |Cite|
|
Sign up to set email alerts
|

An Asthma and Diabetes Quality Improvement Project: Enhancing Care in Clinics and Community Health Centers

Abstract: Asthma and diabetes are major chronic conditions in the United States, particularly in the Medicaid population. The majority of care for these diseases occurs at ambulatory practice sites. The New York State Department of Health Office of Health Insurance Programs (OHIP) worked with IPRO, the New York State Medicare quality improvement organization, to develop and implement a quality improvement project (QIP) for these conditions. The approach was based upon the Chronic Care Model and used an iterative academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The intervention found that patients in the intervention group had improved control of HbA1c, LDL, systolic blood pressure, patient satisfaction, and quality of life (21). Non-randomized studies conducted in PCMH settings found similar results with the diabetes care coordinator being associated with reductions in glycemic control (17, 22) and improvements in CVD risk factors (20, 23) and preventive care measures (24, 25). …”
Section: Elements Of Pcmh That Support Better Diabetes Care and Outcomesmentioning
confidence: 72%
“…The intervention found that patients in the intervention group had improved control of HbA1c, LDL, systolic blood pressure, patient satisfaction, and quality of life (21). Non-randomized studies conducted in PCMH settings found similar results with the diabetes care coordinator being associated with reductions in glycemic control (17, 22) and improvements in CVD risk factors (20, 23) and preventive care measures (24, 25). …”
Section: Elements Of Pcmh That Support Better Diabetes Care and Outcomesmentioning
confidence: 72%
“…Several ongoing programs or disease-related professional organizations have supported intensive efforts to improve influenza vaccination among persons with high-risk conditions (18-21). For example, the Diabetes Quality Improvement Project, a collaborative effort between public and private organizations to improve preventive care for persons with diabetes, including influenza vaccination, has been ongoing for more than 10 years (18, 19).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Diabetes Quality Improvement Project, a collaborative effort between public and private organizations to improve preventive care for persons with diabetes, including influenza vaccination, has been ongoing for more than 10 years (18, 19). The National Asthma Education and Prevention Program panel identified influenza vaccination as one of several “key clinical activities that should be considered as essential for quality asthma care” (20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, community health workers are very effective in counseling to the mothers of their sick children at home, resulting in a 40% reduction in mortality for children less than five years of age (Haines et al, 2007). In the USA, community health centers have a significant role in reducing diabetes and asthma through regular check-ups of urine, blood, and diet (Silver et al, 2011). The critical challenges in the management of local primary health care services include lack of skilled workforce, lack of finance, inadequate transportation and political instability as well (Adeyemo et al, 2005).…”
Section: Service Delivery Of Cc: How Far Does It Meet the Local Demands?mentioning
confidence: 99%